Convergence Analysis of Two Demicontractive Operators - Janwised, Jiraporn; Tunchonnang, Chuanpit; Bunpatcharacharoen, Pheerachate; Akkasriworn, Naknimit (Communications in Mathematics and Applications, 2019)
In this paper, first we introduce a new iterative scheme involving demicontractive mappings in Hilbert spaces which does not require prior knowledge of operator norm and, second, by using the proposed scheme, prove some strong convergence theorems. Finally, we give some numerical examples to illustrate our main result.